Least Criminals for Some Given Conjectures in Group Theory - Sarmin, Nor Haniza; Ilangovan, Sheila (MATEMATIKA, 2004)
In the theory of finite groups, many major theorems have been proved by the minimum counterexample technique or sometimes called “least criminals” technique. It uses the fact that if there is a counterexample to a given theorem, then there is a counterexample of smallest possible order. In this paper, we will find the least criminals for five given conjectures in group theory. Keywords: Least Criminals; Group Theory; Conjectures